Internal control in the economic security system of agricultural and processing organizations - Ostaev , Gamlet Y.; Khosiev, Boris N.; Azrakuliev, Zamir M.; Dzobelova, Valentina B.; Kallagova, Anna Kh (Journal of the University of Zulia, 2022)
The article reveals the need for internal control in the economic security system of agricultural and processing organizations. The objective of the study is to establish the function of internal control in the economic security system of agricultural and processing organizations, as a mechanism for identifying risks and threats. In accordance with this objective, the main task was determined, to substantiate the theoretical and practical aspects of internal control in the economic security system of agricultural and processing organizations. The work examines the substantive and formal methodological aspects, including the study of laws, theories, the structure of scientific knowledge, the analysis of research methods from the point of view of logical structure and the formalized approaches for the construction of the theoretical knowledge, its truth and argumentation. The classification of internal control in the organization’s economic security system is offered. A list of mandatory internal control elements has been determined in the organization’s economic security system. The methods and procedures are grouped by functional components in the economic security system.